What Drives Attitudes toward Immigrants in Sub-Saharan Africa? Evidence from Uganda and Senegal - Malte Becker; Finja Krüger; Tobias Heidland (Institute of Labor Economics (IZA), 2024)
We explore whether attitudes toward immigration and their determinants known from well-studied high-income countries also hold in so far understudied low-income settings where the economic, societal, and geopolitical circumstances differ markedly. Using a causal framework based on experimental and survey data in Uganda and Senegal, we extend the literature by introducing a new concept - power concerns - to test whether perceptions of foreign influence in business and politics affect attitudes toward immigrants. Furthermore, we provide evidence of the perceptions of Chinese immigrants in Africa, whose increasing presence is highly controversial and politicized.
Keywords: F22; O15; O55; 330; attitudes toward immigration; China in Africa; migration; experiment; conjoint